Pengaruh Kepemimpinan Transformasional, Pengalaman Kerja, dan Dukungan Sosial terhadap Kinerja Karyawan PT Putra Sentosa Mandiri - Fery Mayvian Bagaskara; Beny Mahyudi Saputra; Iing Sri Hardiningrum (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
This study aims to analyze the effect of transformational leadership (X1), work experience (X2), and social support (X3) on employee performance (Y) at PT Putra Sentosa Mandiri. This research also seeks to determine the partial effects of each independent variable as well as their simultaneous effect on employee performance. The research method used is a quantitative approach with primary and secondary data sources. The sampling technique applied was saturated sampling, in which the entire population was used as the sample, consisting of 34 employees of PT Putra Sentosa Mandiri. Data were collected through questionnaires, interviews, literature studies, and documentation. The data analysis techniques included validity tests, reliability tests, normality tests, linearity tests, heteroscedasticity tests, multicollinearity tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that transformational leadership has a positive but not significant effect on employee performance, work experience has no positive and insignificant effect on employee performance, while social support has a positive and significant effect on employee performance. Simultaneously, transformational leadership, work experience, and social support do not have a significant effect on employee performance at PT Putra Sentosa Mandiri.